Peningkatan Kapasitas Pemahaman Aparatur Nagari Kamang Hilia Kabupaten Agam tentang Penatausahan, Pelaporan dan Pertanggungjawaban Keuangan Dana Desa - Nurzi Sebrina; Herlina Helmy; Hendri Andi Mesta; Halkadri Fitra; Mike Triani (Manaruko: Jurnal Pengabdian Masyarakat, 2023)
This community service activity in Nagari Kamang Hilia, Agam Regency was motivated by the issuance of Law Number 6 of 2014 and Minister of Home Affairs Regulation Number 20 of 2018 as well as the many village officials in various regions of Indonesia who have legal cases related to the use of village funds. The aim of this activity is to provide understanding for village officials about planning, administration, reporting and accountability of village finances so as to contribute to the creation of a transparent, accountable, participatory, orderly and disciplined nagari financial management system. This activity presents resource persons who are competent in the fields of planning, administration, reporting and accountability as well as supervision of village finances. The activity pattern is carried out in the form of lectures, training and discussions as well as mentoring with 30 participants. The activity ran smoothly and participants' understanding of nagari financial management increased.